2014
DOI: 10.1111/1460-6984.12103
|View full text |Cite
|
Sign up to set email alerts
|

Verbal strategies and nonverbal cues in school‐age children with and without specific language impairment (SLI)

Abstract: Background Considerable evidence suggests that performance across a variety of cognitive tasks is effectively supported by the use of verbal and nonverbal strategies. Studies exploring the usefulness of such strategies in children with specific language impairment (SLI) are scarce and report inconsistent findings. Aim The present study examined effects of induced labelling and auditory cues on the performance of children with and without SLI during a categorization task. Methods & Procedures Sixty-six scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Lidstone, Meins, and Fernyhough (2012) reported that articulatory suppression during a planning task affected children with and without SLI equally, suggesting that children with SLI also use language to mediate their executive function behavior. In contrast, other research has reported that explicitly instructing children with SLI to use language during task performance impedes their performance (Eichorn, Marton, Campanelli, & Scheuer, 2014). Our own data can speak to this relationship as there are significant positive correlations between some of the executive function tasks and SPELT-P 2 and Peabody Picture Vocabulary Test-Fourth Edition standard scores in both the typically developing and SLI groups (see Appendix).…”
Section: Future Directionsmentioning
confidence: 49%
See 1 more Smart Citation
“…Lidstone, Meins, and Fernyhough (2012) reported that articulatory suppression during a planning task affected children with and without SLI equally, suggesting that children with SLI also use language to mediate their executive function behavior. In contrast, other research has reported that explicitly instructing children with SLI to use language during task performance impedes their performance (Eichorn, Marton, Campanelli, & Scheuer, 2014). Our own data can speak to this relationship as there are significant positive correlations between some of the executive function tasks and SPELT-P 2 and Peabody Picture Vocabulary Test-Fourth Edition standard scores in both the typically developing and SLI groups (see Appendix).…”
Section: Future Directionsmentioning
confidence: 49%
“…It may be the case that impaired language is leading to deficits in executive function. For example, children with SLI may be less efficient in using language to mediate their responding on executive function tasks (Eichorn et al, 2014). As an alternative, children's language impairment may be caused, or at lease exacerbated, by their underlying executive function difficulties.…”
Section: Future Directionsmentioning
confidence: 99%
“…The labeling condition resulted in no change in accuracy for the typical children, but led to reduced accuracy among children with SLI. Thus, contrary to findings with typically developing children [39, 40], using language as a task strategy may actually be detrimental for children with SLI [65]. …”
Section: Executive Function In Children With Slimentioning
confidence: 66%
“…Verbal strategy use in SLI was also examined by Eichon, Marton, Campanelli, and Scheuer [65] by comparing performance on a verbal categorization task in a baseline condition to a condition in which children were instructed to label the category aloud. Children with SLI were less accurate than age-matched typical peers in both the baseline and labeling conditions, indicating a relative deficit in categorization.…”
Section: Executive Function In Children With Slimentioning
confidence: 99%
“…Nonlinguistic strategy use may result in poorer performance for children with SLI relative to TD peers in these contexts. On the other hand, capitalizing on the ability to alternate between strategies may support performance on tasks that recruit the visuospatial domain more so than the verbal domain, and prior work suggests that verbal cues may be detrimental to performance for children with SLI under certain task demands (Eichorn et al, 2014;Marton et al, 2014). According to the HCSM, language-based selfreflection provides the opportunity to weigh alternative responses against the habitual response to a task.…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 99%